Literarische Wissenschaftsgeschichte und Wissenschaftstheorie. Kehlmann - Del Giudice - Serres - Malinowski, Bernadette (Literatur- und Naturwissenschaften, 2021)
The book examines the work of Daniel Kehlmann, Daniele del Giudice, and Michel Serres to show how writers' reception of science has engendered a literary epistemology and history of science in the spirit of a poetica scientiae. This new approach subjects questions that science has kept unasked, open, or stifled to meticulous and often surprising ruminations, providing science with a corrective through poetics and hermeneutics.